2016
DOI: 10.1051/matecconf/20167304022
|View full text |Cite
|
Sign up to set email alerts
|

Using Crumb Rubber from Waste Tires to Reduce Road Traffic Noise

Abstract: Abstract. The results of measurements of sound pressure levels on an experimental road section (road pavement with addition of crumb rubber from waste tires) in Mala Ida village (Kosice region, Slovakia) and on a road with stone mastic asphalt in Haniska village (Presov region, Slovakia) are presented in the paper. The results obtained using statistical pass-by methods were compared and they confirmed that road surface with addition of crumb rubber from waste tires produced quieter pavement than stone mastic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“… Infrastrúktúra fejlesztése és karbantartása: Az infrastrúktúra állapötának javítása, példáúl a sínek cseréje, keresztaljak javítása és a pályatörzs karbantartása hatékönyan csökkentheti a zajkiböcsátást [12], [13]. A költségigény ezekben az esetekben általában magasabb lehet, különösen ha nagy területekre és hösszú vasútvönalakra terjednek ki a fejlesztések.…”
Section: A Zajcsillapí Ta S Kö Ltse Geiunclassified
“… Infrastrúktúra fejlesztése és karbantartása: Az infrastrúktúra állapötának javítása, példáúl a sínek cseréje, keresztaljak javítása és a pályatörzs karbantartása hatékönyan csökkentheti a zajkiböcsátást [12], [13]. A költségigény ezekben az esetekben általában magasabb lehet, különösen ha nagy területekre és hösszú vasútvönalakra terjednek ki a fejlesztések.…”
Section: A Zajcsillapí Ta S Kö Ltse Geiunclassified
“…In the review made by Thomas et al [ 124 ], the following common conclusions were found in literature when rubber content increases: compressive strength would be greatly affected, flexural strength is decreased with crumbed rubber or rubber powder and it is increased with rubber fibers, rubberized concrete is more resistant to freeze-thaw test and acid attack, but water absorption increases. Moreover, the increase in ductility and sound absorption makes rubberized concrete suitable to be used in traffic barriers and acoustic panels [ 125 ]. Steel fibers from waste tires enhance mechanical properties at a similar level of industrial steel fibers [ 126 ].…”
Section: Environmentally-driven Admixturesmentioning
confidence: 99%